Modulating oxidative stress: a reliable strategy for coping with community-acquired pneumonia in older adults - Mao, Weixu; Liu, Xuanjun; Fan, Senji; Zhang, Ruibin; Liu, Miao; Xiao, Shunqiong (Frontiers in Medicine, 2025)
Community-acquired pneumonia (CAP) remains one of the leading respiratory diseases worldwide. With the aging of the global population, the morbidity, criticality and mortality rates of CAP in older adults remain high every year. Modulating the signaling pathways that cause the inflammatory response and improve the immune function of patients has become the focus of reducing inflammatory damage in the lungs, especially CAP in older adults. As an important factor that causes the inflammatory response of CAP and affects the immune status of the body, oxidative stress plays an important role in the occurrence, development and treatment of CAP. Furthermore, in older adults with CAP, oxidative stress is closely associated with immune senescence, sarcopenia, frailty, aging, multimorbidity, and polypharmacy. Therefore, multiple perspectives combined with the disease characteristics of older adults with CAP were reviewed to clarify the research progress and application value of modulating oxidative stress in older adults with CAP. Clearly, there is no doubt that targeted modulation of oxidative stress benefits CAP in older adults. However, many challenges and unknowns concerning how to modulate oxidative stress for further practical clinical applications exist, and more targeted research is needed. Moreover, the limitations and challenges of modulating oxidative stress are analyzed with the aim of providing references and ideas for future clinical treatment or further research in older adults with CAP.